Radiocarbon dating for determination of soil organic matter pool sizes and dynamics - Lyon, D. J., author; Peterson, G. A., author; Halvorson, A., author; Leavitt, S. W., author; Follett, R. F., author; Paul, Eldor A., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1997)
The size and turnover rate of the resistant soil organic matter (SOM) fractions were measured by 14C dating and 13C/12C measurements. This involved soils archived in 1948, and recent samples, from a series of long-term sites in the North American Great Plains. A reevaluation of C dates obtained in the 1960s expanded the study scope. The 14C ages of surface soils were modern in some native sites and near modern in the low, moist areas of the landscape. They were much older at the catena summits. The 14C ages were not related to latitude although this strongly influenced the total SOM content. Cultivation resulted in lower C contents and increased the 14C age by an average of 900 yr. The 10- to 20-cm depths from both cultivated and native sites were 1200 year older than the 0- to 10-cm depth. The 90- to 120-cm depth of a cultivated site at 7015 year before present (BP) was 6000 year older than the surface. The nonhydrolyzable C of this depth dated 9035 year BP. The residue of 6 M HCl hydrolysis comprised 23 to 70% of the total soil C and was, on the average, 1500 year older. The percentage of nonhydrolyzable C and its 14C age analytically identify the amount and turnover rate of the old resistant soil C.
Keywords: soil C; N; SOM; organic matter